MANAJEMEN LABA RIIL DAN KETERBACAAN LAPORAN TAHUNAN - Abshari, Firhan Razki; Rahman, Annisaa (Jurnal Akuntansi Kontemporer, 2020)
This study aims to empirically examine the relationship between real earnings man-agement and the company's annual report readability. The population of this research is all companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017 by ex-cluding the financial sector. The sampling technique used was purposive sampling. Data analysis was performed using multiple linear regression with the IBM 25.0 SPSS program. The test results show that real earnings management as measured by abnormal discretional expense proxies and aggregate real earnings management have a negative and significant effect on annual report readability, whereas real earnings management as measured by abnormal cash flow proxy and abnormal production cost does not affect the annual report readability.